2015
DOI: 10.1016/j.gloplacha.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Future projection of Indian summer monsoon variability under climate change scenario: An assessment from CMIP5 climate models

Abstract: In this study, the impact of enhanced anthropogenic greenhouse gas emissions on the possible future changes in different aspects of daily-to-interannual variability of Indian summer monsoon (ISM) is systematically assessed using 20 coupled models participated in the Coupled Model Inter-comparison Project Phase 5. The historical (1951-1999) and future (2051-2099) simulations under the strongest Representative Concentration Pathway have been analyzed for this purpose. A few reliable models are selected based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
169
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(207 citation statements)
references
References 59 publications
21
169
2
Order By: Relevance
“…Overall our results support previous findings that climate projections reveal an increase in monsoon precipitation in the mid-century [54,55] and a possible extension of the monsoon period [56][57][58]. Our results over Northern and Western India and the southeastern coastline differ from previous projections based on the CGCM3.1-PRECIS model chain and the A1B emission scenario [31,59].…”
Section: Enhancing Understanding Of Future Climate Change Impactssupporting
confidence: 88%
“…Overall our results support previous findings that climate projections reveal an increase in monsoon precipitation in the mid-century [54,55] and a possible extension of the monsoon period [56][57][58]. Our results over Northern and Western India and the southeastern coastline differ from previous projections based on the CGCM3.1-PRECIS model chain and the A1B emission scenario [31,59].…”
Section: Enhancing Understanding Of Future Climate Change Impactssupporting
confidence: 88%
“…Meanwhile, the CMIP5 future projections suggest an increase in rainfall over the central Indian subcontinent 26 , though one must note the ongoing debate about whether CMIP5 models are in fact capturing the historic monsoon trends accurately 4,11,12,24 and whether the monsoon projections are reliable in these models 25 . The overall weakening trend of monsoon rainfall over South Asia is a matter of grave concern since the socio-economic livelihood in this region, including agriculture, water resources and power generation are irrevocably dependent on it.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been undertaken [4][5][6][7][8] to study the Indian monsoon rainfall variability in a warming climate. It has been found that all models simulate a stronger seasonal mean monsoon rainfall in the future as compared to the historic period under the strongest warming scenario of RCP 8.5.…”
Section: Introductionmentioning
confidence: 99%